Delayed Replantation of Multiple, Avulsed Maxillary Young Permanent Teeth with Open Apex - Raghavendra, S; Godhi, Brinda Suhas; Veena, R (Journal of Orofacial Research, 2013)
Aim: Aim of this article is to present a case of delayed replantation of multiple, avulsed maxillary permanent teeth that had an extraoral dry time of about 22 hours with 6 month followup. Background: Dental avulsion is a real dental emergency in which prompt management affects the prognosis of the tooth. Avulsed teeth need to be replanted at the earliest in order to insure the best possible prognosis which restores esthetic appearance and occlusal function. However, the long-term survival of replanted avulsed teeth is low due to ankylosis and root resorption. Case description: The patient, aged 9 years old boy, reported almost 22 hours later the road traffic accident in which he lost one deciduous and five permanent teeth. The avulsed teeth were kept in dry environment. Since the patient was young, replantation of the avulsed tooth was planned and performed in the best interest of the patient and to relieve him from psychological, cosmetic and functional trauma. Conclusion: In case of avulsed permanent teeth with prolonged nonphysiological storage, especially in adolescents and young adults, replantation should be performed irrespective of the outcome despite the risk of progressive replacement resorption and subsequent tooth loss.Clinical significance: Reimplantation of avulsed teeth is a standard procedure. However, it has certain limitations. Most often their management is very challenging. This case reportpresents stepwise management of delayed replantation procedure.